2013
DOI: 10.3354/ame01669
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes in picocyanobacterial diversity as revealed by pyrosequencing in temperate waters of the East China Sea and the East Sea

Abstract: To elucidate the seasonal and spatial changes in picocyanobacterial diversity in temperate waters, the abundance and genetic diversity of picocyanobacteria and environmental variables were investigated at 3 stations located in the East China Sea and the East Sea. Barcoded amplicon pyrosequencing of 16S-23S internal transcribed spacer sequences was applied to study picocyanobacterial diversity using 36 samples. Through pyrosequencing, sequences belonging to 27 distinct Synechococcus and Prochlorococcus clades w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
3
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 54 publications
(76 reference statements)
1
39
3
3
Order By: Relevance
“…한반도 주변해역에서 초미소남세균의 분포 연구는 2000년대 중 반에 flowcytometry를 이용하여 시작되었으며, 초미소남세균의 분 자생물학적 방법을 이용한 계통적 다양성 연구도 2000년대 후반에 본격적으로 시작되었다 (Noh et al, 2005;Choi andNoh, 2006, 2009;Choi, 2012;Choi et al, 2013). 이들 연구를 통해 동중국해와 동 해에서 분리된 Synechococcus 균주들의 계통적 다양성 연구가 행 해졌으며 (Choi andNoh, 2006, 2009), 차세대 대량 염기서열 분 석법의 하나인 pyrosequencing 방법을 이용하여 하계 동중국해 북 부 해역 및 동중국해와 동해 초미소남세균 다양성의 계절적 분포 특성을 규명할 수 있었다 (Choi, 2012;Choi et al, 2013).…”
Section: 서 론unclassified
See 2 more Smart Citations
“…한반도 주변해역에서 초미소남세균의 분포 연구는 2000년대 중 반에 flowcytometry를 이용하여 시작되었으며, 초미소남세균의 분 자생물학적 방법을 이용한 계통적 다양성 연구도 2000년대 후반에 본격적으로 시작되었다 (Noh et al, 2005;Choi andNoh, 2006, 2009;Choi, 2012;Choi et al, 2013). 이들 연구를 통해 동중국해와 동 해에서 분리된 Synechococcus 균주들의 계통적 다양성 연구가 행 해졌으며 (Choi andNoh, 2006, 2009), 차세대 대량 염기서열 분 석법의 하나인 pyrosequencing 방법을 이용하여 하계 동중국해 북 부 해역 및 동중국해와 동해 초미소남세균 다양성의 계절적 분포 특성을 규명할 수 있었다 (Choi, 2012;Choi et al, 2013).…”
Section: 서 론unclassified
“…이들 연구를 통해 동중국해와 동 해에서 분리된 Synechococcus 균주들의 계통적 다양성 연구가 행 해졌으며 (Choi andNoh, 2006, 2009), 차세대 대량 염기서열 분 석법의 하나인 pyrosequencing 방법을 이용하여 하계 동중국해 북 부 해역 및 동중국해와 동해 초미소남세균 다양성의 계절적 분포 특성을 규명할 수 있었다 (Choi, 2012;Choi et al, 2013). 이들 연 구를 통해 한반도 주변해에 다양한 clade에 속하는 초미소남세균 이 분포하고, 수온 및 영양염 등이 다양성 분포를 결정하는데 중 요한 요인임을 밝혀냈다.…”
Section: 서 론unclassified
See 1 more Smart Citation
“…Temperature, for example, is one of the most important parameters determining the abundance of Synechococcus (10,16,17). However, to date, only a few studies have reported the temporal changes in the Synechococcus assemblage structure in detail (4,18,19).…”
mentioning
confidence: 99%
“…Temperature, for example, is one of the most important parameters determining the abundance of Synechococcus (10,16,17). However, to date, only a few studies have reported the temporal changes in the Synechococcus assemblage structure in detail (4,18,19).Hong Kong coastal waters have a unique and highly dynamic hydrographic setting and therefore are ideal sites to study the diversity and spatiotemporal variation in the Synechococcus community composition (20). This region is influenced by several different water masses, including the freshwater discharge from the Pearl River, oceanic water of the South China Sea, and the Fujian-Zhejiang coastal current.…”
mentioning
confidence: 99%